2018
DOI: 10.1111/psyg.12365
|View full text |Cite
|
Sign up to set email alerts
|

The hidden patient: chronic physical morbidity, psychological distress, and quality of life in caregivers of older adults

Abstract: Poor physical and mental health among caregivers may impair their ability to provide adequate care to older adults with progressive medical needs. It is important for medical practitioners not to neglect the physical and mental health of caregivers through continued assessment of chronic physical morbidity, psychological distress, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
2
30
0
6
Order By: Relevance
“…Other studies have supported this, showing that informal caregiving for older adults with dementia has a negative effect on the caregivers themselves, such as by increasing loneliness, stress, and social isolation [ 10 , 11 ]; negatively impacting mental and physical health outcomes [ 12 14 ]; and impeding financial potential [ 15 ]. Further, caregivers have been found to self-report lower levels of quality of life and health in general when compared to non-caregivers [ 1 , 9 ] and to have chronic physical conditions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have supported this, showing that informal caregiving for older adults with dementia has a negative effect on the caregivers themselves, such as by increasing loneliness, stress, and social isolation [ 10 , 11 ]; negatively impacting mental and physical health outcomes [ 12 14 ]; and impeding financial potential [ 15 ]. Further, caregivers have been found to self-report lower levels of quality of life and health in general when compared to non-caregivers [ 1 , 9 ] and to have chronic physical conditions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have collected health information by asking participants to check a list including a number of conditions. 22 Whilst these studies consistently suggest a higher burden of physical ill-health in caregivers, an earlier meta-analysis of 23 studies found that stronger relationships occurred with elevated levels of stress hormones, attenuation of numbers of antibodies and poorer global reported health than with other objective disease. 20 For some types of health conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Being accompanied by parents was associated with a 1.93-fold risk of anxiety. A study in Singapore showed that 52.6% of the caregivers of the elderly (≥60 years) had psychological distress [ 22 ] and experienced multiple negative physical, emotional, social, and financial stressors due to the increased demands in care-giving [ 23 , 24 ]. In addition to the above pressures, visiting scholars also worried about their parents becoming infected with COVID-19, because the elderly have had the highest mortality rate from COVID-19 infection [ 25 ].…”
Section: Discussionmentioning
confidence: 99%